Determination Of Legal Remedies For Civil Cases To Make The Principles Of Justice Simple, Fast And Lighting Cost - Andrianantenaina Fanirintsoa Aime; Zulfikar Dori Ad’ha (Law Department, Sharia and Law Faculty., 2021)
One of the principles in the justice system is justice that is simple, fast and low cost. In this regard, the People's Consultative Assembly (MPR) takes this matter seriously and responds to it by issuing a decree, namely TAP MPR No. VIII/MPR/2000 concerning the Annual Report of High State Institutions at the 2000 Annual Session of the People's Consultative Assembly of the Republic of Indonesia, which one of its substances recommends that the Supreme Court immediately resolve delinquent cases by increasing the number and quality of decisions and that the Supreme Court makes regulations to limit entry cassation case. With this principle, it is necessary to conduct a study regarding the application of these principles.